Edukasi Lingkungan Bersih dan Pelatihan Pembuatan Tong Sampah Berbahan Limbah Plastik Bagi Santri TPQ Se Desa Sukoharjo Kediri - Nurjannah, Fitrotun (LP3M IAIFA Kediri, 2024)
Islam is very concerned about cleanliness so that a Muslim should keep himself, his clothes, and his environment clean. In reality, cleanliness is still a problem that we need to pay attention to. The research approach used in this research is the PAR or Participatory Action Research method. Participatory Action Research (PAR) is a qualitative approach that integrates methods and techniques of observing, documenting, analyzing and interpreting the characteristics, patterns, attributes and meanings of the human phenomenon under study. PAR is a collaborative process between research, education and action, including in Islamic Education Institutions, one of which is TPQ which will be used as a research site is TPQ Shirotul Jannah which is located in the hamlet of Puhrejo Sukoharjo village, Kayen Kidul sub-district. Based on the researcher's experience, there is still a lot of garbage scattered in the yard, and the recitation room is dirty and dusty. Based on this, we held a